3(x-2)(x+1)=0

Simple and best practice solution for 3(x-2)(x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)(x+1)=0 equation:


Simplifying
3(x + -2)(x + 1) = 0

Reorder the terms:
3(-2 + x)(x + 1) = 0

Reorder the terms:
3(-2 + x)(1 + x) = 0

Multiply (-2 + x) * (1 + x)
3(-2(1 + x) + x(1 + x)) = 0
3((1 * -2 + x * -2) + x(1 + x)) = 0
3((-2 + -2x) + x(1 + x)) = 0
3(-2 + -2x + (1 * x + x * x)) = 0
3(-2 + -2x + (1x + x2)) = 0

Combine like terms: -2x + 1x = -1x
3(-2 + -1x + x2) = 0
(-2 * 3 + -1x * 3 + x2 * 3) = 0
(-6 + -3x + 3x2) = 0

Solving
-6 + -3x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(-2 + -1x + x2) = 0

Factor a trinomial.
3((-1 + -1x)(2 + -1x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {-1, 2}

See similar equations:

| -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 |

Equations solver categories